2018
DOI: 10.1097/iae.0000000000001744
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ranibizumab for the Treatment of Choroidal Neovascularization Due to Uncommon Cause

Abstract: Supplemental Digital Content is Available in the Text.Ranibizumab was effective in treating choroidal neovascularization of various etiologies, with a treatment effect of +9.9 letters versus sham at Month 2 and a mean gain of 11.0 letters from baseline to Month 12. The beneficial effects of ranibizumab were observed across all etiology subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 57 publications
4
67
0
10
Order By: Relevance
“…However, it is important to point out that patients with choroidal neovascularization resulting from CSC have shown to benefit from anti-VEGF treatment. 43 Currently in the European Union, ranibizumab 0.5 mg is approved for the treatment of visual impairment resulting from choroidal neovascularization (regardless of the underlying etiology) in adult patients. 43,44 Because of a lack of a differential diagnosis, it was not possible to assess the reason for lack of treatment effect of anti-VEGF in the subgroup with idiopathic disease (ocular vascular disorder, n ¼ 1; idiopathic chorioretinopathy, n ¼ 36) at month 2, which represented 29% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to point out that patients with choroidal neovascularization resulting from CSC have shown to benefit from anti-VEGF treatment. 43 Currently in the European Union, ranibizumab 0.5 mg is approved for the treatment of visual impairment resulting from choroidal neovascularization (regardless of the underlying etiology) in adult patients. 43,44 Because of a lack of a differential diagnosis, it was not possible to assess the reason for lack of treatment effect of anti-VEGF in the subgroup with idiopathic disease (ocular vascular disorder, n ¼ 1; idiopathic chorioretinopathy, n ¼ 36) at month 2, which represented 29% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…43 Currently in the European Union, ranibizumab 0.5 mg is approved for the treatment of visual impairment resulting from choroidal neovascularization (regardless of the underlying etiology) in adult patients. 43,44 Because of a lack of a differential diagnosis, it was not possible to assess the reason for lack of treatment effect of anti-VEGF in the subgroup with idiopathic disease (ocular vascular disorder, n ¼ 1; idiopathic chorioretinopathy, n ¼ 36) at month 2, which represented 29% of the patients. The overall treatment effect at the primary end point showed no benefit for ranibizumab versus sham (À0.49 letters; 37 patients received ranibizumab and 14 patients received sham treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Originating in choroidal blood vessels, this disease is usually associated with other fundus pathology [1]. It has been suggested that when abnormal blood vessels originating from the choriocapillaris break through the Bruch membrane and grow in the retinal pigment epithelium (RPE) or infiltrates into the subretinal pigment epithelium or subretinal space [2,3], they can result in CNV. CNV that develops in younger patients who are less than 50 years old is usually attributed to pathologic myopia, angioid streaks, trauma, cytomycosis, central serous chorioretinopathy (CSC) and other hereditary ocular diseases [4,5].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Studie MINERVA hodnotila účinnost léčby ranibizumabem u 119 pacientů s CNV z jiných příčin než VPMD a u patologické myopie v režimu léčby PRN [13]. Výsledky hodnocení NKZO ukazují, že v průběhu ročního sledování došlo ke zlepšení o 9,5 písmen ETDRS optotypů při průměrném počtu 5,8 injekcí ranibizumabu (vstupní hodnoty NKZO byly 62,4 písmen).…”
Section: Diskuseunclassified
“…Pozoruhodné je, že pacienti s myopickou CNV dostali během 12ti měsíců průměrně o 26,8 % méně injekcí (průměrně 4,1) než pacienti ve skupině CNV z jiných příčin (prů-měrně 5,6). Naše výsledky nicméně jsou v tomto poměru v souladu s výsledky jiných studií [11,12,13,16,18,19]. Vysvětlit to můžeme tím, že myopická CNV má převážně klasickou složku (typ 2 CNV) na rozdíl od CNV při VPMD a CNV z jiných příčin, která rychleji reaguje na léčbu inhibitory VEGF [21].…”
Section: Diskuseunclassified